International Capital Markets : Developments and Prospects, 1984 - Watson, Maxwell (Occasional Papers; Occasional Paper ;, 1984)
This paper provides a description and analysis of recent developments in international capital markets and an assessment of the prospects for private financing flows, in particular to the developing countries.